2005
DOI: 10.1680/cien.2005.158.6.52
|View full text |Cite
|
Sign up to set email alerts
|

Electrical energy storage—a review of technology options

Abstract: Matching uneven generation patterns to varying demands for power requires flexibility in the power network. Electrical energy storage technologies now exist to complement mature generation types as well as new forms of renewable generation. Electrical energy storage can also support network management. This paper presents examples of electrical energy storage applications, together with the development status of several technologies, and introduces the regulatory, economic and commercial aspects of combining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…However, crossover and ohmic losses due to the large distances between positive and negative electrodes limited the coulombic efficiency. Although the Mn(acac) 3 system shows a lower open-circuit potential (1.1 V) than that of V(acac) 3 , Cr(acac) 3 , and VRB, it exhibits better reversibility both for Mn(II)/Mn(III) and Mn(III)/Mn(IV) redox couples, with a columbic efficiency approaching 97% in a static H-type cell. Shinkle et al studied the degradation mechanisms in the non-aqueous V(acac) 3 redox systems [80], and showed that environmental oxygen and water are associated with side reactions that affect the long-term charge-discharge response of the battery.…”
Section: Non-aqueous Redox-flow Batteriesmentioning
confidence: 96%
See 3 more Smart Citations
“…However, crossover and ohmic losses due to the large distances between positive and negative electrodes limited the coulombic efficiency. Although the Mn(acac) 3 system shows a lower open-circuit potential (1.1 V) than that of V(acac) 3 , Cr(acac) 3 , and VRB, it exhibits better reversibility both for Mn(II)/Mn(III) and Mn(III)/Mn(IV) redox couples, with a columbic efficiency approaching 97% in a static H-type cell. Shinkle et al studied the degradation mechanisms in the non-aqueous V(acac) 3 redox systems [80], and showed that environmental oxygen and water are associated with side reactions that affect the long-term charge-discharge response of the battery.…”
Section: Non-aqueous Redox-flow Batteriesmentioning
confidence: 96%
“…As a promising technology for storing intermittent renewable energy, VRB systems have received perhaps the most attention of all RFBs [16,[27][28][29][30][31][32][33][34][35][36][37][38][39]. In fact, prototypes up to the range of MW in power and MWh in energy-storage capacity have been demonstrated [3,35,[40][41][42][43][44][45][46][47]. Figure 5 shows the 5-10 kW VRB stack developed by Skyllas-Kazacos' group along with its general efficiencies.…”
Section: All-vanadiummentioning
confidence: 99%
See 2 more Smart Citations
“…Today in the industry there exists a multitude of suggested technologies, so-called energy storage systems (ESS) which are used for this purpose. Based on the form in which the energy is stored, these energy storage systems can be divided into the electrical, which comprises capacitors, super-capacitors; mechanical, which includes flywheels, pumped hydroelectric systems, compressed air; chemical, can be hydrogen or other chemical storage; thermal, like hot water, molten salts and electrochemical, which comprises of batteries [4].…”
mentioning
confidence: 99%